1997
DOI: 10.1074/jbc.272.41.25433
|View full text |Cite
|
Sign up to set email alerts
|

The Human Uncoupling Protein-3 Gene

Abstract: Uncoupling protein-3 (UCP3) is a recently identified candidate mediator of adaptive thermogenesis in humans. Unlike UCP1 and UCP2, UCP3 is expressed preferentially and at high levels in human skeletal muscle and exists as short and long form transcripts, UCP3 S and UCP3 L . UCP3 S is predicted to encode a protein which lacks the last 37 C-terminal residues of UCP3 L . In the present study, we have defined the intron-exon structure for the human UCP3 gene and determined that UCP3 S is generated when a cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 167 publications
(60 citation statements)
references
References 30 publications
1
57
0
1
Order By: Relevance
“…The structure of the UCP2 and UCP3 genes is similar to that of the UCP1 gene, the coding sequence being distributed over six exons in each of the three genes. However, the UCP2 and UCP3 genes differ from the UCP1 gene by the presence of two or one untranslated exons located on the 5h side of the UCP2 and UCP3 gene respectively [146][147][148][149][150][151]. The structure of the genes of plant UCPs is somewhat different, since nine exons covering the coding sequence were detected in the gene encoding AtUCP (M. Laloi, unpublished work).…”
Section: Genetics Of Ucpsmentioning
confidence: 99%
See 4 more Smart Citations
“…The structure of the UCP2 and UCP3 genes is similar to that of the UCP1 gene, the coding sequence being distributed over six exons in each of the three genes. However, the UCP2 and UCP3 genes differ from the UCP1 gene by the presence of two or one untranslated exons located on the 5h side of the UCP2 and UCP3 gene respectively [146][147][148][149][150][151]. The structure of the genes of plant UCPs is somewhat different, since nine exons covering the coding sequence were detected in the gene encoding AtUCP (M. Laloi, unpublished work).…”
Section: Genetics Of Ucpsmentioning
confidence: 99%
“…Following the initial cloning of UCP2 and UCP3 cDNAs, it was observed that these two genes are within less than 100 kb of each other [57,146,155]. In fact, it was demonstrated that the two genes are adjacent, the UCP2 gene being only 7 or 8 kb downstream of the UCP3 gene in mouse and human respectively [149,151,156].…”
Section: Genetics Of Ucpsmentioning
confidence: 99%
See 3 more Smart Citations